The pregnancy in neurofibromatosis 1: A retrospective register‐based total population study. Issue 10 (16th August 2017) - Leppävirta, Jussi; Kallionpää, Roope A.; Uusitalo, Elina; Vahlberg, Tero; Pöyhönen, Minna; Timonen, Susanna; Peltonen, Juha; Peltonen, Sirkku
Abstract : The objective of this retrospective total population study was to form a view of the pregnancies of the patients with neurofibromatosis type 1 (NF1). A cohort of 1, 410 Finnish patients with NF1 was acquired by searching NF1‐related inpatient and outpatient hospital visits and confirming the diagnoses by reviewing the medical records. Ten matched control persons per patient with NF1 were collected from Population Register Centre. Study persons were linked to data from Medical Birth Register and Care Register for Health Care through the personal identity code. Cesarean deliveries, hypertension/preeclampsia, and placental abruptions were more common among mothers with NF1 with adjusted odds ratios of 2.24 (95%CI 1.63–3.07), 1.96 (95%CI 1.18–3.24), and 13.40 (95%CI 4.26–42.13), respectively. The adjusted mean pregnancy duration was 0.65 (95%CI 0.42–0.88) weeks shorter among the mothers with NF1 than in the control group consisting of non‐NF1 mothers giving birth to a non‐NF1 child. The pregnancies of non‐NF1 mothers giving birth to a NF1 child were 0.43 (95%CI 0.24–0.62) weeks shorter than in the control group. In summary, NF1 of the mother was associated with a shortened pregnancy and increased pregnancy complications. Also, the NF1 of the fetus slightly shortened pregnancy. Since mothers with NF1 are at increased risk for pregnancy complications, careful evaluation of their pregnancies is warranted.